PERAN MEDIASI KEPUASAN KERJA PADA PENGARUH PERSON JOB FIT DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL GRAND INNA DI KUTA - Dewi, Luh Putu Alda Meysintia; Martadiani, Media; Suarka, I.B. Komang (Warmadewa Management and Business Journal (WMBJ), 2024)
The purpose of this research is to determine and analyze the mediating role of job satisfaction on the influence of job suitability and job training and employee performance at the Grand Inna Hotel in Kuta. Kuta Grand Inna Hotel has a population and sample of 158 employees and the samples uses a saturated sampling technique. All data obtained by distributing questionnaires is suitable for use and then analyzed using the SEM-PLS program. From the research results, it was concluded that 1) Person job fit has a positive and insignificant effect on employee performance, 2) Job training has a positive and insignificance effect on employee performance, 3) Person job fit has a positive and significant effect on job satisfaction, 4) Job training positive and significance effect on job satisfaction, 5) Job satisfaction has a positive and significant effect on employee performance, 6) Job satisfaction can mediate the effect of person job fit on employee performance, 7) Job satisfaction can mediate the effect of job training on employee performance. This research recommends that companies pay attention to problems that can affect employee performance so that employees can make a big contribution to the company so that the company’s goals are achieved.